Socio-cultural determinants of trauma and the problem with PTSD - Womersley, Gail (My University, 2016)
Between 1998 and 2006, 65% of medical reports submitted to Swiss authorities in support of asylum claims were based on psychiatric diagnoses, most notably PTSD (Lechenne, 2012). However, PTSD is a diagnosis developed in the West with questionable cross-cultural validity and politically loaded legal implications for asylum seekers. By medicalizing trauma on an individual level based on single events of the past, such diagnoses risk rendering us blind to other ongoing aspects of interpersonal, political and social violence on a more global scale, including significant post migration factors such as the asylum seeking process itself, which may be deemed equally traumatic by migrants (Maier & Straub, 2011; D. Silove, Steel, McGorry, & Mohan, 1998; Derrick Silove, Steel, & Watters, 2000). However, there is also evidence that mental health problems such as PTSD could have a negative impact on asylum seekers’ credibility through affecting the consistency of their verbal accounts of their experiences – thereby creating potential bias against a person genuinely fleeing persecution (Rogers, Fox, & Herlihy, 2015; Turner, 2015). It is therefore argued that a more informed understanding of social and cultural manifestations of trauma and its consequences should play a critical role in informing public health interventions as well as legal policy.
, NCCR Onthemove 2nd annual conference: Changing Realities of Migration and Mobility. A Swiss Perspective., Neuchatel